Kontingenčna teorija strateškega poslovodnega računovodstva - Čadež, Simon (Naše gospodarstvo, 2006)
In the past two decades, revisions of management accounting practices have produced a variety of novel approaches in the fields of costing, strategic investment appraisal, and strategic control and performance management. It is often argued that the developments at the level of individual techniques have given rise to a whole new discipline called "strategic management accounting." The present study aims to investigate the impact of the strategic managament accounting system on organizational performance. Building on the central proposition of contingency theory, a systems approach was used to empirically assess the validity of contingency theory. The systems approach takes a holistic view of fit and seeks to examine the effects on performance of internally consistent multiple contingencies. To operationalize this approach, cluster analysis was used. The results, based on the data from 193 large Slovenian companies, show that contingency theory is valid. Superior performance is not automatically associated with a sophisticated accounting system, but rather it is a product of an appropriate fit between an accounting system and contingency factors.
Keywords: management; podjetja; poslovodenje; računovodstvo; računovodske informacije; Slovenia; Slovenija